The impact of exposure to HPV related information and injunctive norms on young women's intentions to receive the HPV vaccine in China: A structural equation model based on KAP theory - Wang, Yi; Chen, Yubing; Bao, Sheng (Frontiers in Public Health, 2023)
Background The HPV vaccination is a crucial line of defensing against cervical cancer. As a result of government support and positive publicity from the majority of media, a craze for HPV vaccination has occurred in China. Besides, the intentions to get the HPV vaccine among women of appropriate age is also influenced by families' and friends' attitudes and perceptions toward HPV vaccine. Therefore, the purpose of this study was to investigate how HPV related information exposure and injunctive norms affect young Chinese women's intentions to receive the HPV vaccine. Methods A structural equation model was developed based on KAP theory, and 567 effective questionnaires were collected through an online survey. We used SPSS 26.0 for the reliability and validity analysis and the differential testing of demographic characteristics, and Amos 26.0 for the goodness-of-fit analysis and paths testing of the model. Results Our findings showed that (1) intention to receive HPV vaccine differed significantly in age (P = 0.046), educational background (P = 0.001), and occupation (P = 0.004). (2) Exposure to HPV related information positively affected knowledge about HPV (β = 0.316, P < 0.001) and intention to receive HPV vaccine (β = 0.141, P < 0.001). (3) Knowledge about HPV positively affected attitude toward HPV vaccine (β=0.341, P < 0.001), but negatively affected intention to receive HPV vaccine (β = −0.148, P < 0.05), and attitude toward HPV vaccine positively affected intention to receive HPV vaccine (β = 0.594, P < 0.001). (4) Injunctive norms positively affected attitude toward HPV vaccine (β = 0.362, P < 0.001) and intention to receive HPV vaccine (β = 0.420, P < 0.001). Conclusions Exposure to HPV related information influenced young Chinese women's intentions to receive the HPV vaccine and related knowledge, that is, the more frequently they were exposed to HPV related information, the stronger their intentions to receive the vaccine and the higher their HPV knowledge. Also, the perception and support of HPV vaccination by people around them will further influence their attitudes and intentions to receive the HPV vaccine.